1985
DOI: 10.2166/wst.1985.0127
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic Anaerobic Contact Digestion of Palm Oil Mill Effluent

Abstract: The palm oil industry is one of the major agro-based industries in Malaysia whose production accounts for more than 90% of the world export. The industry, however, also generates enormous quantities of liquid waste with high organic load causing serious pollution problems. In view of the high level of organics, anaerobic pretreatment is usually practised prior to aerobic breakdown. Most of the anaerobic digesters installed at the mills are currently operated under mesophilic conditions. However, the inherently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
1
20
1
Order By: Relevance
“…This despite that Blaak (1981) reported that the addition of 27 mg nitrogen and 13.5 mg P 2 O 5 /g bacteria dried solids were essential for the anaerobic digestion of POME in order to stimulate CH 4 production. It was found by Ibrahim et al (1985) that in the 50 C digester, only about 10e100 sulphate-reducing bacteria/ml were detectable whereas in the digester operating at 30 C, a count of between 3 Â 10 4 and 4 Â 10 4 sulphate-reducing bacteria/ml was observed (Toerien et al, 1968). This finding has an important implication on the utilization of biogas for generating electricity through gas engine systems where low concentrations of the highly corrosive H 2 S in biogas are desirable.…”
Section: Anaerobic Suspended Growth Processesmentioning
confidence: 95%
See 1 more Smart Citation
“…This despite that Blaak (1981) reported that the addition of 27 mg nitrogen and 13.5 mg P 2 O 5 /g bacteria dried solids were essential for the anaerobic digestion of POME in order to stimulate CH 4 production. It was found by Ibrahim et al (1985) that in the 50 C digester, only about 10e100 sulphate-reducing bacteria/ml were detectable whereas in the digester operating at 30 C, a count of between 3 Â 10 4 and 4 Â 10 4 sulphate-reducing bacteria/ml was observed (Toerien et al, 1968). This finding has an important implication on the utilization of biogas for generating electricity through gas engine systems where low concentrations of the highly corrosive H 2 S in biogas are desirable.…”
Section: Anaerobic Suspended Growth Processesmentioning
confidence: 95%
“…Thermophilic anaerobic digestion of POME has been tried previously (Borja-Padilla and Banks, 1993;Cail and Barford, 1985b;Chin and Wong, 1983;Ibrahim et al, 1985;Yeoh, 1986) since it would be advantageous to carry out the anaerobic digestion under thermophilic conditions within the temperature range of 49e57 C (McCarty, 1964) with the POME temperature varying between 45 and 70 C. It is generally recognized that thermophilic operation has the potential for a faster bacterial growth and consequently higher treatment rates. For example, by operating the digester under thermophilic conditions (Cail and Barford, 1985b), the rate was four times faster than that achieved by Cail and Barford (1985a) when a similar digester was operated at 35 C.…”
Section: Anaerobic Suspended Growth Processesmentioning
confidence: 99%
“…This result supports the idea raised by Murto et al (2004) who reported that co-digestion could improve biogas production by 50-200%, depending on the operating condition and substrates used. Also, based on Ibrahim et al (1984) anaerobic digestion of POME alone will affect its methanogenesis process as restricting steps. Methanogenesis is very important in anaerobic digestion because it is the terminal step of producing biogas.…”
Section: Biogas Productionmentioning
confidence: 99%
“…In addition to the empty fruit bunches, 1-2.5 t of wastewater with a COD of 50-65 g·l -1 is released per tonne of palm oil (Ibrahim et al 1984;Ny et al 1985). The energy content of the wastewater could be utilized if the wastewater was digested in biogas reactors.…”
Section: Complex Biogenic Wastes For Compost and Biogas Productionmentioning
confidence: 99%
“…The energy content of the wastewater could be utilized if the wastewater was digested in biogas reactors. A thermophilic digestion process would be the most feasible procedure, due to the high initial temperature of the effluents (70-80C) and the high ambient temperature in the tropics, which prevents rapid cooling to the mesophilic temperature range (Ibrahim et al 1984). Anaerobic digestion in the thermophilic temperature range would favour bioavailability of oil by emulsification of palm oil residues.…”
Section: Complex Biogenic Wastes For Compost and Biogas Productionmentioning
confidence: 99%